PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, DAN LIKUIDITAS TERHADAP KINERJA KEUANGANPADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERCATAT DI BURSA EFEK INDONESIA (BEI)TAHUN 2013-2017 - Dwi Puji Rahayu (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2019)
The purpose of this study was to determine the effect of firm size, capital structure and liquidity as well as knowing which factors are dominant on the financial performance of food and beverage companies listed on the Indonesian stock exchange (BEI) in 2013-2017.This type of research is quantitative causal.The population in this study were all companies consuming food and beverage sub-sectors listed on the Indonesian stock exchange (BEI) as a sample ( purposive sampling) of 13 companies.Independent variables: firm size (X1) capital structure (X2) and liquidity (X3) dependent variable financial performance (Y)Data collection techniques use observation.Data were analyzed using multiple linear analysis assisted with the help of SPSS version 22. The results of this study indicate that there is influence of firm size (X1) capital structure (X2) and liquidity (X3) simultaneously or partially on financial performance (Y) in food companies and beverages listed on the Indonesian Stock Exchange (IDX).The dominant factor in this regression model is the company size variable.For owners of companies on the Stock Exchange it is recommended that a strategy is developed to increase the effectiveness of company size, capital structure and liquidity because all three have a significant effect on financial performance and for investors it is advisable to consider the ratios related to company size, capital structure and liquidity because it can reflect the company's financial performance prospects those on the IDX.